SEMIOTIC ANALYSIS IN WILLIAM BLAKE POEMS - Husnul Hatima Adudu; Dahlia Husain (Universitas Muhammadiyah Gorontalo, 2019)
Semiotic Analysis in William Blake Poems. The problem in this research is how to apply Riffaterre’s theory. This research focused on semiotic of Riffaterre’s theory in William Blake poems, titled The Sick Rose, My Pretty Rose Tree, and The Garden of Love. The method that used in this research was descriptive qualitative method. The data that used in this research was a written record in the form of three poems by William Blake. Three poems in question were The Sick Rose, My Pretty Rose Tree, and The Garden of Love. The technique used to collect data in this research was the technique of reading log. The researcher used the Riffaterre’s theory to analysis the poems. Based on the analysis, it can be concluded that poem The Sick Rose and The Garden of love depict of live before France Revolution occurred, and poem My Pretty Rose Tree describe about the author’s feeling to his wife.